Problematika Pembelajaran Bahasa Arab Di Madrasah Ibtidaiyah - Aliyya Laubaha, Siti; Yasin, Zohra; Zikran Adam, Muhammad (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to find out the various applications that can be utilized and used by teachers in learning Arabic. This study uses the method of literature (library research). The author obtains data through books, journals, articles related to research. This study analyzes the data by describing the results obtained. The results of the research are that currently there are many applications that support the learning process in accordance with current developments in science and technology. In the 4.0 to 5.0 era, educators are required to be able to operate the available educational technology so that learning can be easier and more interesting, not just monotonous so that students feel bored and bored. Therefore, applications are provided to support learning. Especially in learning foreign languages ​​such as Arabic. The applications used include duolingo, canva, youtube, mu'jam al-ma'any, edmodo, arabic unlocked, online arabic program, learning arabic speak arabic, secil, drops, memrise, kahoot, and facebook.